Determination Of Quality Of Milk From Different Genotype Of Dairy Cows (Bangladesh Journal of Animal Science, 2012)
The present study was conducted to investigate the milk quality from different genotype. A total 48 dairy cows belong to different genotypes such as Holstein cross, Jersey cross, Sahiwal cross and Red Chittagong were selected. Milk compositional viz. specific gravity, Acidity test, Fat test, Protein test, Solids-not-fat (SNF) test and total solids (TS) test were carried out. It was observed that the higher specific gravity of milk was obtained from Jersey cross and Red Chittagong genotype, which was significantly higher (P